The EFFECT OF MEME IMAGE MEDIA FOR SPEAKING SKILL IN ENGLISH LEARNING AT SMA NEGERI 7 KOTA JAMBI - Agustian; Resi Seilvia (Journal Of Language Education and Development (JLed), 2025)
This research aims to determine the effect of meme image for speaking skill in English learning at the eleventh grade student at SMAN 7 Kota Jambi. This study uses a quantitative approach with a quasi-experimental design. This research uses three concepts, namely pre-test, treatment and post-test. The pre-test would be carried out before giving treatment, the treatment would be carried out in five meetings, and post-test would be given after treatment. The results of data analysis showed that the mean of post-test both experimental and control class are different, they are 75.00 and 65.75. The result of t-test obtained is 0.000 ≤ α = 0.10. The result indicated the alternative hypothesis was accepted and the null hypothesis was rejected. This finding shows that the meme image has significant effect on students' speaking skills. Based on the findings, could be said that the media picture is very useful for teachers to improve students' speaking skills, and easy to learn for students.